2008
DOI: 10.12693/aphyspola.114.1417
|View full text |Cite
|
Sign up to set email alerts
|

Non-Exponential Photoionization of the DX Centers in Gallium Doped CdTe and Cd0.99Mn0.01Te

Abstract: The low temperature non-exponential transients of photoconductivity build-up in gallium doped Cd0.99Mn0.01Te and CdTe alloys possessing DX centers were studied. It was found that the two-exponential model commonly used to explain the persistent photoconductivity growth in semiconductors with DX centers describes properly solely the photokinetics obtained for CdTe:Ga. In the case of Cd 0.99 Mn 0.01 Te:Ga the stretched-exponential approach is more appropriate, for it explains the short-time power-law exhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…Within the stochastic approach to relaxation processes it can be shown that the observed stretched-exponential power-law asymptotic property observed for large b remains in agreement with those described by formula (10). According to the fact that the relaxation rate density and the relaxation time density are related, it follows from (6), (8) and (9) that the relaxation time pdf may also be given in terms of a series representation, i.e.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Within the stochastic approach to relaxation processes it can be shown that the observed stretched-exponential power-law asymptotic property observed for large b remains in agreement with those described by formula (10). According to the fact that the relaxation rate density and the relaxation time density are related, it follows from (6), (8) and (9) that the relaxation time pdf may also be given in terms of a series representation, i.e.…”
Section: Resultssupporting
confidence: 64%
“…Property (10) denotes that the effective rate distribution in the KWW relaxation pattern is scale-invariant. The distribution looks the same at each length scale, i.e.…”
Section: Mathematical Description Of Stretched-exponential Relaxationmentioning
confidence: 99%
“…According to the calculations carried out in [2] the shallow Ga state should be metastable with respect to the deep state also for Ga doped CdTe. Recently persistent photoeffects have been observed by us for gallium doped CdTe [3,4] confirming this theory. However there are no reports on the DX-linked trap in this compound.…”
Section: Introductionsupporting
confidence: 66%
“…[2] that in the time domain persistent photoconductivity build-ups for gallium doped Cd 1−x Mn x Te mixed crystals follow the KWW relaxation pattern, whereas gallium doped CdTe samples exhibit double-exponential behavior. The non-exponentiality of photoconductivity transients in Cd 1−x Mn x Te and CdTe results from the presence of deep metastable defectsthe so-called DX centers which are related to gallium (Ga) atoms.…”
Section: Introductionmentioning
confidence: 90%